1993
DOI: 10.1128/mcb.13.6.3773-3781.1993
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Hsp83 RNA Localization during Drosophila Oogenesis and Embryogenesis

Abstract: Hsp83 is the Drosophila homolog of the mammalian Hsp90 family of regulatory molecular chaperones. We show that maternally synthesized Hsp83 transcripts are localized to the posterior pole of the early Drosophila embryo by a novel mechanism involving a combination of generalized RNA degradation and local protection at the posterior. This protection of Hsp83 RNA occurs in wild-type embryos and embryos produced by females carrying the maternal effect mutations nanos and pumilio, which eliminate components of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…As chaperones, HSPs are known to be highly expressed in response to environment stress, as well as to the presence of hormones (Xu, Xiao, Xia, Murphy, & Huang, 2010). Hsp83 has been associated with embryogenesis and oogenesis in D. melanogaster (Ding, Parkhurst, Halsell, & Lipshitz, 1993), and with the facilitation of nuclear import of the JH receptor Methoprene‐tolerant in the presence of JH, leading to Kr‐h1 expression (He et al, 2014). In a previous project we had found another member of the HSP family, Hsp90 , as highly expressed in larval queen ovaries and also as exhibiting a strong JH‐treatment response in larval worker ovaries (Lago et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As chaperones, HSPs are known to be highly expressed in response to environment stress, as well as to the presence of hormones (Xu, Xiao, Xia, Murphy, & Huang, 2010). Hsp83 has been associated with embryogenesis and oogenesis in D. melanogaster (Ding, Parkhurst, Halsell, & Lipshitz, 1993), and with the facilitation of nuclear import of the JH receptor Methoprene‐tolerant in the presence of JH, leading to Kr‐h1 expression (He et al, 2014). In a previous project we had found another member of the HSP family, Hsp90 , as highly expressed in larval queen ovaries and also as exhibiting a strong JH‐treatment response in larval worker ovaries (Lago et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…RNA localization occurs primarily through three distinct mechanisms: diffusion and entrapment, best exemplified by nanos mRNA in the Drosophila oocyte ( Forrest and Gavis, 2003 ); protection from degradation, as typified by Hsp83 mRNA in the Drosophila embryo ( Ding et al, 1993 ); or active transport, as observed for many RNAs, including ASH1 mRNA in budding yeast ( Long et al, 1997 ; Takizawa et al, 1997 ; Bertrand et al, 1998 ). Active transport involves the trafficking of a cargo, such as an RNP, connected via adaptor proteins to molecular motors, which translocate on actin or microtubule cytoskeletal tracks ( Bullock, 2011 ).…”
Section: Delivering the Message: How Rnas Localizementioning
confidence: 99%
“…For example, localization-dependent mRNA degradation has been described for Hsp83 and nanos. Their mRNAs are degraded throughout Drosophila eggs via the Smaug-mediated recruitment of deadenylation complex but remain stable at the posterior pole 54,55 . Previous studies reported local processing of miRNAs 56 and modification of the components of the miRNA pathway in response to synaptic activity [57][58][59] .…”
Section: Discussionmentioning
confidence: 99%